1997
DOI: 10.1074/jbc.272.35.22046
|View full text |Cite
|
Sign up to set email alerts
|

A Kinase Domain-truncated Type I Receptor Blocks Bone Morphogenetic Protein-2-induced Signal Transduction in C2C12 Myoblasts

Abstract: Members of the transforming growth factor (TGF)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 53 publications
3
52
0
1
Order By: Relevance
“…TGF-␤ and BMP-2 block the myogenic differentiation of C2C12 cells by suppressing the expression of master control genes, including that of MyoD (20,35). Our data show that overexpression of Runx2 suppresses MyoD expression and stops the myogenic differentiation of C2C12 cells (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…TGF-␤ and BMP-2 block the myogenic differentiation of C2C12 cells by suppressing the expression of master control genes, including that of MyoD (20,35). Our data show that overexpression of Runx2 suppresses MyoD expression and stops the myogenic differentiation of C2C12 cells (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Alkaline Phosphatase Staining-Alkaline phosphatase (ALP) activity has been widely accepted as a simple and easiest way to determine the osteogenic differentiation, especially in the BMP-2-induced osteogenic transdifferentiation in C2C12 cells (3,6,7). Cells were washed with phosphate-buffered saline twice, fixed with 2% paraformaldehyde, and stained for alkaline phosphatase according to the manufacturer's instructions (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…BMPR-I is further subclassified into BMPR-IA (also called ALK3) and BMPR-IB (also called ALK6). It has been shown that both the inhibition of myoblast differentiation and the induction of osteoblast differentiation by BMP-2 involve the activations of BMPR-I receptors (6,7), their intracellular transducers Smad1 and Smad5 (8,9), and the osteogenic master transcription factor Runx2 (4,10).…”
mentioning
confidence: 99%
“…cells, BMP-6 mainly utilizes ALK-2, whereas BMP-2 utilizes ALK-3 for signaling (19), because ALK-6 is not expressed in these cells (19,30). We thus examined the effects of I-Smads on BMP-6-and BMP-2-induced signaling in C2C12 cells (Fig.…”
Section: Effect Of Smad6 On Bmp-6-induced Alk-2 Activation and Bmp-2-mentioning
confidence: 99%